(untitled) (ҚазҰУ хабаршысы. Экология сериясы, 2016)
Status of the main commercial marine fish stocks in the Caspian Sea is analyzed in the work. Problems of distribution, abundance, qualitative population structure of common sprat, anchovy kilka, big-eyed kilka, Dolginsk herring, Caspian shed, big-eyed shed, silverside and mullet (long-finned mullet) are considered. Based on received materials recommendations for presumable size of commercial catch of concerned biologigal water object are given. It was stated that modern sprat fishery catches minimum amount of anchovy and big-eyed kilka. Their number has extremely shortened, the effectiveness of natural spawning has reduced, commercial stocks are coming down rapidly. Environmental degradation in the Caspian Sea starting at the beginning of the 21st century, caused by the immigration of ctenophoran mnemiopsis, waterquakes and water eutrophication conduced diseases of anchovy kilka, which appeared in appearance of splanchnic tumors. The volumes of commercial catch are not going to increase in the short term. Effectiveness of reproduction of common spart is annually set at the long-time average annual level. Commercial stocks are increasing, it is recommended to increase the size of commercial catch of this species. It is reasonable to increase the number of commercialfishing gears at Dagestan seaside. The stocks of sea herring are at the stable level, dolginsk herring has the most abundance. The replenishment of populations is determined by existence of forage organisms and water temperature in the southern par of the Caspian sea. Silverside is caught by common sprat harvesting. The stocks are stable, it is recommended to increase species catching. There is only one mullet species is known in harvesting, it is long-finned mullet. Its stocks are stable, the volume of commercial catch is determined by catching management. Raw material resources of marine fish (except for anchovy and big-eyed kilka) let to increase their commercial catch.